2005
DOI: 10.1093/humrep/dei021
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyosis in endometriosis—prevalence and impact on fertility. Evidence from magnetic resonance imaging

Abstract: With a prevalence of up to 90%, uterine adenomyosis is significantly associated with pelvic endometriosis and constitutes an important factor of sterility in endometriosis presumably by impairing uterine sperm transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
262
3
32

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(302 citation statements)
references
References 37 publications
5
262
3
32
Order By: Relevance
“…The cause of adenomyosis is unknown, but interesting theories have considered adenomyosis a pathology of the endo-myometrial junctional zone, and have attempted to explain the association of adenomyosis with subfertility and endometriosis [73,74].…”
Section: Adenomyosismentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of adenomyosis is unknown, but interesting theories have considered adenomyosis a pathology of the endo-myometrial junctional zone, and have attempted to explain the association of adenomyosis with subfertility and endometriosis [73,74].…”
Section: Adenomyosismentioning
confidence: 99%
“…These peristaltic disorders of the junctional zone have also been linked to dysmenorrhoea and menorrhagia, and may play a role in the pathogenesis of endometriosis by facilitating retrograde menstruation and implantation of viable endometrial cells into the abdominal cavity [73,81]. Pelvic endometriosis, especially in severe stages, is also strongly associated with junctional zone thickening [73,74,83,84]. Observational studies suggest that perturbations in junctional zone structure or functions before conception predispose towards a spectrum of fertility and obstetrical complications [85].…”
Section: The Endo-myometrial Junctional Zonementioning
confidence: 99%
“…17,19,21,[29][30][31] The aim of our study was to evaluate the JZ ultrasound features in patients with endometriosis. We tried to detect a correlation between endometriosis and adenomyosis in the case of JZ modifications.…”
Section: Commentmentioning
confidence: 99%
“…6,16,17 Pelvic endometriosis, especially in severe stages, also is associated strongly with JZ thickening. [18][19][20][21] Therefore, the evaluation of JZ and its alterations by noninvasive imaging seems very important especially in patients with endometriosis.…”
mentioning
confidence: 99%
“…Today, evidence is accumulating that also the presence of endometriosis is accompanied by JZ abnormalities and there is extensive literature demonstrating that endometriosis, particularly in more severe stages, is associated with structural changes in the JZ or inner myometrium, including increased thickness and adenomyosis [39][40][41][42] . In addition, studies of the JZ in women with endometriosis showed that modifications leading to the development of adenomyosis, represented by an increased diameter of the dorsal JZ of the uterus at magnetic resonance imaging, had already commenced early in the third decade of life and, in these women, progressed steadily during the fourth decade 43 .…”
Section: Reunifying the Two Conditionsmentioning
confidence: 99%